Polish validation of soft skills questionnaire for nurses - Katarzyna Tomaszewska; Krystyna Kowalczuk; Marek Sobolewski; Bożena Majchrowicz (Frontiers in Public Health, 2025)
IntroductionThe professional competence of nurses is a pivotal factor in ensuring patient safety and significantly influences the quality of care delivered. In line with the guidelines of the International Council of Nurses and the World Health Organization, educational programs for nursing professionals must emphasize the development of both psychosocial and psychomotor competencies to maintain high training standards. Additionally, effective quality management in healthcare institutions necessitates continuous monitoring of nurses' competencies, encompassing not only practical skills but also interpersonal abilities.AimThe aim of this study was to translate and adapt the Soft Skills Questionnaire for Nurses into a Polish-language version and to evaluate its reliability and validity as an instrument for assessing nurses' soft skills.Material and methodsThe validation study was conducted from April to June 2024 among a cohort of 496 actively practicing nurses in Poland. A two-stage validation process was employed. The first stage involved the linguistic and cultural adaptation of the original questionnaire into Polish, following formal authorization from the original authors. The second stage entailed a psychometric evaluation of the translated instrument. Participants completed the questionnaire twice, with a 1-month interval between administrations to assess test-retest reliability. The internal consistency of each subscale was evaluated using Cronbach's alpha coefficient. Agreement between the two sets of responses was analyzed by calculating descriptive statistics for both time points, followed by assessment of the differences using the Wilcoxon signed-rank test. The strength and direction of association between the two administrations were examined using Spearman's rank correlation coefficient. Additionally, test-retest reliability was assessed using the intraclass correlation coefficient (ICC), providing further evidence of the tool's stability over time.Results and conclusionsThe questionnaire comprised three distinct subscales designed to evaluate key domains of soft skills: communication skills (NCS—Nursing Communication Skills), confidentiality (CON—Confidentiality), and management and emotional intelligence (MEI—Management and Emotional Intelligence). The internal consistency of the NCS subscale was relatively high, with a Cronbach's alpha coefficient of 0.669, approaching the commonly accepted threshold of 0.70 for satisfactory reliability. The CON subscale demonstrated a slightly lower internal consistency (α = 0.601), while the MEI subscale yielded the lowest internal consistency (α = 0.544), suggesting potential variability in item coherence within this domain. Despite these moderate reliability indices, all additional statistical analyses supported the robustness of the questionnaire. The Wilcoxon signed-rank test revealed no statistically significant differences between the test and retest administrations (p > 0.05), indicating the absence of systematic response shifts over time. Furthermore, Spearman's rank correlation coefficients between the two administrations were exceptionally high (rs > 0.90), and test-retest reliability, as assessed by the intraclass correlation coefficient (ICC), also exceeded 0.90 across all subscales. These findings indicate that the Polish adaptation of the Soft Skills Questionnaire for Nurses demonstrates strong temporal stability and satisfactory psychometric performance, supporting its suitability for use in both clinical assessments and empirical research on soft skills within the nursing profession.